Income Effects on the Trade Balance - Kim, Yoonbai (The Review of Economics and Statistics, 1996)
This paper investigates the income effects on the trade balance with particular attention to the distinction between permanent and transitory disturbances for the United States, Japan, Germany, and the United Kingdom. In all four countries, movements in the trade balance have mostly been associated with transitory changes in income. The latter also are negatively associated with the trade balance. In marked contrast, permanent changes in income have little to do with the trade balance. These results are examined in light of intertemporal models and real business cycle models. Copyright 1996 by MIT Press.